Impact of ultrasonic treatment on rice starch and grain functional properties: A review - Bonto, Aldrin P.; Tiozon, Rhowell N.; Sreenivasulu, Nese; Camacho, Drexel H. (Elsevier, 2021)
As a green, nonthermal, and innovative technology, ultrasonication generates acoustic cavitation in an aqueous medium, developing physical forces that affect the starch chemistry and rice grain characteristics. This review describes the current information on the effect of ultrasonication on the morphological, textural, and physicochemical properties of rice starch and grain. In a biphasic system, ultrasonication introduced fissures and cracks, which facilitated higher uptake of water and altered the rice starch characteristics impacting textural properties. In wholegrain rice, ultrasonic treatment stimulated the production of health-related metabolites, facilitated the higher uptake of micronutrient fortificants, and enhanced the palatability by softening the rice texture. This review provides insights into the future direction on the utilization of ultrasonication for the applications towards the improvement of rice functional properties.